Recombinant Human Thyroid Stimulating Hormone versus Thyroid Hormone Withdrawal for Radioactive Iodine Treatment of Differentiated Thyroid Cancer with Nodal Metastatic Disease - Wolfson, Robert M. (J Oncol, 2016)
Introduction. Recombinant human thyroid stimulating hormone (rhTSH) is approved for preparation of thyroid remnant ablation with radioactive iodine (RAI) in low risk patients with well differentiated thyroid cancer (DTC). We studied the safety and efficacy of rhTSH preparation for RAI treatment of thyroid cancer patients with nodal metastatic disease. Methods. A retrospective analysis was performed on 108 patients with histopathologically confirmed nodal metastatic DTC, treated with initial RAI between January 1, 2000, and December 31, 2007. Within this selected group, 31 and 42 patients were prepared for initial and all subsequent RAI treatments by either thyroid hormone withdrawal (THW) or rhTSH protocols and were followed up for at least 3 years. Results. The response to initial treatment, classified as excellent, acceptable, or incomplete, was not different between the rhTSH group (57%, 21%, and 21%, resp.) and the THW group (39%, 13%, and 48%, resp.; P = 0.052). There was no significant difference in the final clinical outcome between the groups. The rhTSH group received significantly fewer additional doses of RAI than the THW group (P = 0.03). Conclusion. In patients with nodal-positive DTC, preparation for RAI with rhTSH is a safe and efficacious alternative to THW protocol.